2019
DOI: 10.3324/haematol.2018.205856
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow adipose tissue-derived stem cell factor mediates metabolic regulation of hematopoiesis

Abstract: Hematopoiesis is dynamically regulated by metabolic cues in homeostatic and stressed conditions; however, the cellular and molecular mechanisms mediating the metabolic sensing and regulation remain largely obscure. Bone marrow adipose tissue remodels in various metabolic conditions and has been recently proposed as a niche for hematopoietic stem cells after irradiation. Here, we investigated the role of marrow adipose tissue-derived hematopoietic cytokine stem cell factor in unperturbed hematopoiesis by select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 72 publications
2
36
0
Order By: Relevance
“…Inactivity increases MAT, which can impair hematopoiesis by occupying space and/or through paracrine action 58 . Tight reciprocal relationship between MAT and hematopoiesis 59 , 60 support that adipocytes are negative regulators of hematopoietic stem cell 55 . Low EPO has also been shown to favor adipogenesis 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Inactivity increases MAT, which can impair hematopoiesis by occupying space and/or through paracrine action 58 . Tight reciprocal relationship between MAT and hematopoiesis 59 , 60 support that adipocytes are negative regulators of hematopoietic stem cell 55 . Low EPO has also been shown to favor adipogenesis 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stromal cells’ secretion of SCF has been instead associated with appropriate homing of HSPCs ( Horwitz et al, 2011 ). Mainly secreted by BM adipocytes and Lepr+ stromal cells, studies on mice have proven that SCF is essential for HSPC regeneration as well as hematopoiesis and cell homeostasis, particularly in conditions of obesity and aging ( Zhang et al, 2019 ; Zhou et al, 2017 ). Inhibition of the appropriate interactions between SCF receptor and ligand has shown to enhance HSPC clearance, confirming the chemokine role in HSPCs’ self-renewal ( Czechowicz et al, 2007 ).…”
Section: Mesenchymal Stromal Cells’ Hematopoietic Supportmentioning
confidence: 99%
“…Perivascular stromal cells and endothelial cells are crucial components of the HSC niche, which is highlighted by the fact that both cell types secrete SCF [24]. Moreover, BM adipocytes are also a major supplier of SCF [27] and a study in mice with an adipocyte-specific knockout revealed that MAT-derived SCF is essential for hematopoiesis both under steady state and metabolic stress conditions [28].…”
Section: Our Bones Are Full Of Fat-but Why?mentioning
confidence: 99%